How to immerse a child into music – media in supporting acculturation of a small child during music classes based on E.E. Gordon theory - Justyńska, Martyna; Majewska-Owczarek, Anna (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
The text discusses the issue of musical acculturation of a young child in the Edwin Elias Gordon’s concept of teaching music in the time of distance learning, which is difficult for most parents and teachers. The authors of the article reflected on online music education of children, looking at this issue in the context of the advantages and disadvantages of such a solution. The official public Facebook profiles dealing with music education based on E.E. Gordon’s theory were analyzed. The teachers did not give up the parents’ support in the process of teaching music to their children, offering them ditties and rhythm songs, suggestions for joint music making and concerts. The form of online classes did not allow to create musical dialogue between the teacher and the class participant, but it became a way for the child to listen to a variety of music presented from the recording, as well as it allowed the parent to involve more consciously in the process of developing their child’s musical abilities. According to the authors, the Gordon classes conducted online have therefore gained a wider context as an opportunity to fill in a larger space in the family activities.